Unani System of Medicine - Ahmad, Bilal; Akhtar, Jamal (Pharmacognosy Reviews)
The Unani physician believes that the healthy state of the human body is maintained by a power known as Tabiyat or Quwwat-e-Mudabbira (medicatrix naturae), gifted to it from its creator. The concept of Tabiyat is much vaster than the concept of immunity system of body. It controls, regulates and restores the physiological mechanisms of the body and helps in potentiating the immunity of the body and its resistance against various ailments. Suppression of this gifted power leads to disease. Therefore, the duty of the physician is to use such methods/treatments that encourage the body’s own innate healing response (Tabiyat). This can be achieved by stimulating the Hararat-e-Ghariziya (Vital force of body), which is decreased in a diseased person making him vulnerable to environmental and pathological challenges.